High-performance ECRH at W7-X: experience and perspectives. (30th August 2021) - Laqua, H.P.; Baldzuhn, J.; Braune, H.; Bozhenkov, S.; Brunner, K.; Hirsch, M.; Hoefel, U.; Knauer, J.; Langenberg, A.; Marsen, S.; Moseev, D.; Pasch, E.; et al.
Abstract: The second operation phase of W7-X (OP1.2) showed the potential of exclusively electron cyclotron resonance heating (ECRH)-sustained plasma operations in stellarators. Employing multi-pass ECRH scenario in the second harmonic O-mode (O2-ECRH), stationary densities of up to 1.4 × 10 20 m −3 could be achieved. This scenario also made stationary divertor detachment possible, which is a reactor-relevant scenario for power and particle exhaust. At high densities and with sufficiently high density gradients for an improved ion confinement, the coupling between the electrons and ions was strong enough to bring the ion temperature to values above 3 keV and to the neoclassical limit for some magnetic configurations, thus enabling to test the W7-X neoclassical optimization. The planned enhancement of the ECRH performance will enable to advance towards reactor-relevant beta values and to investigate their stability and confinement of fast particles, which is a priority goal of W7-X.